2014
DOI: 10.1183/09031936.00063014
|View full text |Cite
|
Sign up to set email alerts
|

Neural respiratory drive and breathlessness in COPD

Abstract: The aim of this study was to test the hypothesis that neural respiratory drive, measured using diaphragm electromyogram (EMGdi) activity expressed as a percentage of maximum (EMGdi%max), is closely related to breathlessness in chronic obstructive pulmonary disease. We also investigated whether neuroventilatory uncoupling contributes significantly to breathlessness intensity over an awareness of levels of neural respiratory drive alone.EMGdi and ventilation were measured continuously during incremental cycle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 49 publications
8
83
1
3
Order By: Relevance
“…Our study adds measurement of EAdi, reflecting motor output of the central nervous system to the diaphragm muscle (American Thoracic Society/European Respiratory Society, 2002), which causes contraction of the diaphragm. EAdi is thereby a more specific and sensitive reflective of neural respiratory drive than V E , which could also be influenced by mechanical properties of the respiratory system (Jolley et al, 2015). Herrera and Kazemi studied the Fig.…”
Section: Effect Of Elevated Plasma Bicarbonate On Respiratory Drivementioning
confidence: 99%
See 2 more Smart Citations
“…Our study adds measurement of EAdi, reflecting motor output of the central nervous system to the diaphragm muscle (American Thoracic Society/European Respiratory Society, 2002), which causes contraction of the diaphragm. EAdi is thereby a more specific and sensitive reflective of neural respiratory drive than V E , which could also be influenced by mechanical properties of the respiratory system (Jolley et al, 2015). Herrera and Kazemi studied the Fig.…”
Section: Effect Of Elevated Plasma Bicarbonate On Respiratory Drivementioning
confidence: 99%
“…First, the respiratory drive, represented by the electrical activity of the diaphragm (American Thoracic Society/European Respiratory Society, 2002; Jolley et al, 2015), is decreased with increasing arterial bicarbonate levels, resulting in a decreased V E . This is different from the findings of Oren in 1991; that study showed no difference in minute ventilation related to P et CO 2 between pre and post sodium bicarbonate administration (arterial bicarbonate from 25.5 ± 0.6 to 30.6 ± 1.7 mEq/l in 3 days) (Oren et al, 1991).…”
Section: Effect Of Elevated Plasma Bicarbonate On Respiratory Drivementioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, EMGdi signals were recorded using a five-pair oesophageal electrode catheter, which has been acknowledged as an ideal method to quantify NRD since it is not easily disturbed by other respiratory muscles and not affected by electrode movement and lung volume change (8)(9)(10)(11)(12)(13). However, oesophageal electrode placement is an invasive test and may hinder its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated an increase in neural respiratory drive (NRD) in COPD patients (7)(8)(9)(10), which is principally due to adverse pulmonary mechanics requiring an increased drive to maintain ventilation. However, the actual ventilation tends to descend.…”
Section: Introductionmentioning
confidence: 99%